PERLINDUNGAN DAN PENGELOLAAN WILAYAH KAWASAN PESISIR DAN PULAU-PULAU KECIL BERDASARKAN UU NO. 27 TAHUN 2007 - Sadriyah Mansur (Madani Legal Review, 2019)
The birth of Law Number 27 Year 2007 about Protected Area Management Of Small Island And Coastal basically show the same management regime of coastal and marine resources of Indonesia, which encouraged privatization of coastal waters and small islands of Indonesia, through the Coastal Concessions (HP-3). The result showed that the protection and environmental management in coastal regions and small islands, especially on HP-3 set forth in Article 16 up to Article 20, namely: the utilization is given in the form of HP-3 covering the surface of the sea and pool water up to the surface of the sea floor, HP-3 is given in area and time, must pay attention to the preservation of ecosystems, indigenous peoples, national interests, as well as the right of innocent passage for foreign ships, HP-3 is given to individuals, badah law, and indigenous peoples, given for a period of 20 years and can be extended up to two times, the HP-3 can be switched, transferred and pledged debt.